Functional Outcome and Quality of Life After Surgical Fixation of Tibial Plateau Fracture in a Tertiary Care Center of Nepal - Thapa, Jagadish; Parajuli, Bikash; Shrestha, Rohit; Kayastha, Sabik Raj; Acharya, Nabaraj; Pandey, Sudarshan (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Functional outcome and quality of life (QoL) of patients will change following tibial plateau fracture fixation. There are limited studies evaluating functional and radiological outcomes following tibial plateau fixation in Nepal, and none has evaluated QoL. We aim to evaluate functional outcome and QoL in patients with tibial plateau fracture with a follow up period of more than two years. Methods This was a cross sectional, observational study done at Dhulikhel Hospital, from August 2021 to January 2022. Western Ontario and McMaster Universities Arthritis Index (WOMAC) functional outcome and World Health Organization QoL-8 (WHOQoL-8) questionnaire were filled by patients operated for tibial plateau fracture from 2011 to 2019. Compound fractures, untraceable patients, and those managed with casts were excluded from the study. Results There were 121 patients (male: female = 2.3:1) with a mean age of 37.1 years. Road traffic accidents (44.6%) were the most common mode of injury, and Schatzker type IV (30.6%) was the most common type of fracture. The average WOMAC score was 13.05±12.1 and the average WHOQoL-8 score was 30.24±4.1. The average WOMAC score in high-energy and low energy trauma patients were 17.07±12.29 and 8.21±10 respectively. The average WHOQoL-8 in high energy and low energy trauma patients were 29.28±3.59 and 31.38±4.38 respectively. Conclusions Surgical reduction and stable internal fixation of tibial plateau fractures with long term follow up has a good functional outcome and quality of life. High energy trauma is associated with poor functional outcome and quality of life.